The Anti-depression Effect of Angelicae Sinensis Radix Is Related to the Pharmacological Activity of Modulating the Hematological Anomalies - Gong, Wenxia; Zhu, Shiwei; Chen, Congcong; Yin, Qicai; Li, Xiao; Du, Guanhua; Zhou, Yuzhi; Qin, Xuemei (Frontiers in Pharmacology, 2019)
Angelicae Sinensis Radix (AS), a well-known herb in traditional Chinese medicine (TCM), has been wildly used for replenishing the blood and promoting circulation, in Asia for thousands of years. It has been confirmed that AS also possesses the pharmacological activity of anti-depression. At the same time, recent studies suggested that depression is associated with anemia, and depression could be ameliorated via modulating the blood system. However, it is still unknown whether the anti-depression effect of AS is related to its pharmacological activity of modulating the blood system. In the current study, hematological examination and metabonomic techniques were performed to explore potential anti-depression mechanisms of AS, related to the function of modulating the blood system in a chronic unpredictable mild stress (CUMS) model. The results demonstrated that AS could significantly improve CUMS-induced depressive symptom, hematological anomalies, and hypoxia symptoms. The analysis of metabonomics demonstrated that 26 potential biomarkers in depression could be regulated by the administration of AS. Among them, eight biomarkers participate in the metabolic pathways of amino acid and sphingolipid, and energy metabolism could also be regulated in an anemia model through the administration of AS, as reported in previous literatures. Further results proved that AS modulated energy metabolism in depression through the inhibition of the expression of pyruvate dehydrogenase lipoamide kinase isozyme 1 (PDK-1) and lactate dehydrogenase A (LDHA). These results suggested that the modulation of the blood system was involved in the anti-depression effect of AS. The mechanism may be associated with the promotion of the body’s energy metabolism, the stabilization of cell membranes, the promotion of serum protein synthesis, and the enhancement of immunity.